The Economic Impact of the Covid-19 Pandemic on SMEs in Selected Sub - Saharan African Economies: An Empirical Approach - Grimbald, Ndah; Ziraba, Abdallah; Martha, Abeja Ekure; Henry, Jong Ketuma (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The Covid-19 outbreak is having substantial economic effects and wreaking havoc on sub-Saharan Africa. The pandemic has unleashed a unique combination of shocks to global commodity markets, disrupting the global supply chain and impacting supply and demand simultaneously. SMEs in lower income countries and particularly in sub-Sahara Africa are bearing the brunt of the economic hardship brought about by Covid-19. To this effect, the purpose of this study is to determine the economic impact the Covid-19 outbreak has on small and medium size (SMEs) enterprises across selected sub-Sahara African economies using an empirical approach to analysis. The phenomenon under study is objectively determined and the source of acceptable knowledge is positivism epistemology. The research approach is a deductive one and the axiological underpinning is value-free. The research paradigm is quantitative method of analysis. A sample of 500 participants from four focus groups namely the Transport sector; Hotels bars & restaurants; retail stores; & tourism sector were randomly selected in Cameroon, Uganda, Nigeria and Zimbabwe. Secondary data was also sourced from the IMF, World Bank, OECD, and AU. Four causal relationships were hypothesized and the findings revealed that financial risks, poor economic performance of SMEs, loss of jobs and rising unemployment have a significant positive impact on the survival of SMEs in sub-Sahara Africa. The main impact of the Covid-19 pandemic will depend on its severity and duration but the consequences are likely to be long lasting.